2012
DOI: 10.1590/s1415-52732012000600005
|View full text |Cite
|
Sign up to set email alerts
|

Índice de qualidade da dieta de mulheres usuárias de um programa de atividade física regular "Academia da Cidade", Aracajú, SE

Abstract: OBJETIVO: Avaliar a qualidade da dieta de mulheres praticantes de atividades físicas do Programa Academia da Cidade segundo idade e estado nutricional, Aracajú, Sergipe. MÉTODOS: Foram coletados dados sociodemográficos, antropométricos e dietéticos de 169 mulheres. O Índice de Qualidade da Dieta foi obtido a partir da média de aplicação de dois recordatórios de 24 horas. Os dados do Índice de Qualidade da Dieta total e de seus componentes foram analisados de acordo com o índice de massa corporal (obesos e não … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
2
0
4
Order By: Relevance
“…Study outcomes and index scores were found in 28 studies: seven of these evaluated the relationship of the index with socioeconomic and demographic factors and food items 17,[31][32][33][34][35][36] ; eight studies evaluated the relationship with socioeconomic factors and health [37][38][39][40][41][42][43][44] ; five studies evaluated the relationship with health outcomes [45][46][47][48][49] ; four studies evaluated the relationship with nutrients [50][51][52][53] ; two studies evaluated the relationship with some type of intervention 15,54 ; one study evaluated the relationship with nutrients and food items 55 ; and one study evaluated the relationship with socioeconomic and demographic factors 56 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study outcomes and index scores were found in 28 studies: seven of these evaluated the relationship of the index with socioeconomic and demographic factors and food items 17,[31][32][33][34][35][36] ; eight studies evaluated the relationship with socioeconomic factors and health [37][38][39][40][41][42][43][44] ; five studies evaluated the relationship with health outcomes [45][46][47][48][49] ; four studies evaluated the relationship with nutrients [50][51][52][53] ; two studies evaluated the relationship with some type of intervention 15,54 ; one study evaluated the relationship with nutrients and food items 55 ; and one study evaluated the relationship with socioeconomic and demographic factors 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers use the term Healthy Eating Index [13][14][15][18][19][20][21]23,24,[27][28][29][30][31]33,34,[36][37][38]40,42,[45][46][47]50,[52][53][54] , while other studies refer to the Dietary Quality Index 11,12,17,22,25,26,32,35,39,41,43,44,48,49,51,55,56 . Some authors referred to using the Dietary Quality Index when they published in Brazilian journals and the Healthy Eating Index when they published in international journals, reinforcing the lack of standardization in relation to nomenclatures regarding indices.…”
Section: Discussionmentioning
confidence: 99%
“…Constatou-se ainda, como um dos desafios em alguns estudos, a escassez de iniciativas de aconselhamento de modos saudáveis de vida à população na APS. Portanto, notase que é necessário fortalecer a atuação do ACS na promoção à saúde e prevenção de doenças (16)(17) . de exercícios físicos, devendo-se incrementar no plano de cuidado, sua inserção nas demais redes de atenção, se assim for necessário (18) .…”
Section: Segundo O Manual De Atenção àS Pessoas Com Sobrepeso Eunclassified
“…Em população de mulheres (n=169) acompanhadas pelo Programa Academia da Cidade de Aracaju, em Sergipe, constatou-se média de escore de 66,6 pontos para o IQD 26 . A partir disso, evidenciou-se a importância de constantes estratégias educacionais voltadas à nutrição na efetivação de uma vida mais saudável para toda a população, principalmente para as praticantes de atividade física regular, já que buscam no exercício físico benefícios para a obtenção de hábitos saudáveis, manutenção ou busca pelo peso corporal ideal e, assim, a prevenção de DCNT associadas.…”
Section: ▄ Discussãounclassified